2013
DOI: 10.1016/j.bodyim.2013.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Body size dissatisfaction and avoidance behavior: How gender, age, ethnicity, and relative clothing size predict what some won’t try

Abstract: Sixty-eight percent of U.S. adults are overweight/obese, and this epidemic has physical, psychosocial, and behavioral consequences. An internet sample of adults (N = 2997) perceiving themselves as larger than ideal in clothing size reported their body mass index (BMI), relative clothing size (RS; discrepancy between current and ideal size), and avoidance behaviors. Exploratory factor analysis of 10 avoid-ance items produced social avoidance and body display avoidance factors. A relative importance analysis rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 46 publications
2
12
2
1
Order By: Relevance
“…For instance, although our findings are consistent with the notion that individuals who are dissatisfied with their appearance protect themselves by avoiding social interactions (Maphis et al, 2013;Myers & Rosen, 1999;Puhl & Brownell, 2003), several of our findings suggest that this strategy may be unhelpful. First, lack of social interaction was predictive of subsequent increases in state body dissatisfaction.…”
Section: Discussioncontrasting
confidence: 67%
“…For instance, although our findings are consistent with the notion that individuals who are dissatisfied with their appearance protect themselves by avoiding social interactions (Maphis et al, 2013;Myers & Rosen, 1999;Puhl & Brownell, 2003), several of our findings suggest that this strategy may be unhelpful. First, lack of social interaction was predictive of subsequent increases in state body dissatisfaction.…”
Section: Discussioncontrasting
confidence: 67%
“…5,8,17 Satisfactory levels of physical appearance and body may place great impacts on college-age female's adoption of appearance management strategies such as dressing and weight management. 4,6,16 However, such behaviors may back fire if there is no thorough understanding of the fondness and concerns of their body and the mechanism behind. 11 This study confirms that college-age females in the United States and China have different of fondness and dissatisfaction toward their different body parts.…”
Section: Resultsmentioning
confidence: 99%
“…This is an issue worth scrutiny because body satisfaction influences multiple aspects of an individual's life, 1−4 from daily routines such as clothing choices to physical and mental health. Previous studies have shown that females, particularly young females, experience much higher pressure to pursue and meet certain physical beauty standards compared to males; 1,5,6 therefore, females practice a greater amount and variety of appearance management behaviors than males. 4,7 A majority of existing studies focus on the dieting or cosmetic surgery behaviors that can make long-term changes to a person's physical body.…”
Section: Introductionmentioning
confidence: 99%
“…Body avoidance behaviors constituted the second subscale of SAS-PPW. Postpartum women adopted avoidance behaviors, possibly as a consequence of body depreciation (Maphis et al, 2013). Previous studies have pointed out that the postpartum period was associated with negative feelings due to women's concerns and expectations about regaining their pre-gestational body dimensions (Clark et al, 2009;Patel et al, 2005).…”
Section: Discussionmentioning
confidence: 99%